Past and present geomorphological hazard and cultural heritage loss in El Castellar castle scarp (Central Ebro Basin, Spain) - Peña Monné, José Luis (2023)
The ruins of the Medieval castle and village of El Castellar are located on an abrupt 1.2-km-long scarp of Miocene gypsums, in the central sector of the Ebro depression. The Medieval remains of the main El Castellar castle are perched on a 100 m cliff on the Ebro River. Considering the historical and geoarchaeological relevance of El Castellar settlement, this investigation aimed to study the geomorphological hazards and paleoenvironmental context of the site during and after the settlement and its later evolution, including its current state. To afford this objective the geomorphological context was determined analyzing the dynamics of each scarp sector. Geomorphological data suggest that in Medieval times its constructions were favored by the Medieval Climatic Anomaly (MCA) environmental conditions. During that times, the Ebro River was located in a centered position on its floodplain, and lateral alluvial fans protected the scarp from basal erosion. Later, during the Little Ice Age (LIA), great climatic flows and recurrent floods changed the river dynamics and promoted the river channel movement against the scarp, destabilizing its foot and generating large landslides and rockfalls, thus promoting its retreat. The village buildings and castle at the top of the scarp were seriously damaged. For several reasons, the area is not easily accessible, but it still contains a relevant archaeological heritage that deserves to be studied and preserved.